2022
DOI: 10.1097/jxx.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

Primary care nurse practitioner practices to lower type 2 diabetes risks in women with a history of gestational diabetes mellitus

Abstract: Background: Women with a gestational diabetes mellitus (GDM) history have increased lifetime type 2 diabetes (T2D) risk, with 16 times greater risk 3 to 6 years after the pregnancy, compared with women without GDM. Offspring from diabetes-complicated pregnancies also face increased health risks.Purpose: The study purpose was to describe the primary care practices of nurse practitioners (NPs) aimed at reducing T2D-related health risks in women with a history of GDM.Methodology: Florida-licensed primary care NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
2
0
0
Order By: Relevance
“…Hyperglycemia from GDM is transient and short‐lived and may not be long enough to initiate or exacerbate PD. As a result, periodontitis patients are likely to be the cause of GDM and not a result of it 25–28 . The results of the present meta‐analysis also confirm this hypothesis and confirm the development of GDM in pregnant women with periodontitis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Hyperglycemia from GDM is transient and short‐lived and may not be long enough to initiate or exacerbate PD. As a result, periodontitis patients are likely to be the cause of GDM and not a result of it 25–28 . The results of the present meta‐analysis also confirm this hypothesis and confirm the development of GDM in pregnant women with periodontitis.…”
Section: Discussionsupporting
confidence: 82%
“…As a result, periodontitis patients are likely to be the cause of GDM and not a result of it. [25][26][27][28] The results of the present meta-analysis also confirm this hypothesis and confirm the development of GDM in pregnant women with periodontitis. The meta-analysis results of Lima et al in 2015 showed that there is no positive and significant relationship between periodontitis and GDM, which contradicts the results of the present meta-analysis.…”
Section: Discussionsupporting
confidence: 81%